Ordering and selecting production rules for constraint maintenance: complexity and heuristic solution - Fraternali, P.; Paraboschi, S. (IEEE transactions on knowledge and data engineering, 1997)
Presents a technique for analyzing the run-time behavior of integrity constraint repair actions, i.e. active database rules that are specifically designed to correct violations of database integrity. When constraints become violated due to an incorrect user transaction, rule computation is started to restore the database to a correct state. Since repair actions may be numerous and may conflict with each other, automated support for the analysis of their run-time behavior is necessary. The proposed technique helps the rule base administrator define a repair rule selection strategy such that the computation terminates for every input transaction, the final database state satisfies all the constraints, and the user's preferences among different ways to restore integrity are taken into account. In addition, it can be used by the rule designer to spot "dangerous" rules that may be subject to redesign. This problem is formulated as an optimization problem on directed hypergraphs, which we demonstrate to be NP-hard and which we solve by means of a heuristic algorithm.